Dolgoročne spremembe okolja 1 - Andrič, Maja (Opera Instituti Archaeologici Sloveniae, 2012)
Changes of past and present environment of Slovenia are discussed in nine papers, which were written by 21 authors, coming from 14 research organisations. Our aim is to increase multidisciplinary communication and cooperation between Slovenian researchers, working in the fields of palaeoecology and ecology. Research topics include: archaeozoology, biology, ecology, geoarchaeology, palynology, nature protection, dendrochronology, archaeobotany, geochemistry, Karst research and geography.